Tissue analysis for drug development - Ho, Stacy (Future Science Ltd (Unitec House, 2 Albert Place, London N3 1QB, UK), 2013)
In the six chapters of this book, the authors highlight the critical aspects and considerations of tissue analysis. They summarize the general principles and processes in tissue analysis with useful and practical information so that the reader is then able to identify the critical factors and address their own particular challenges.